A contrastive Study of Requesting in English and Vietnamese Conversations - Nguyễn Thuận Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The speech act of request is among the most common behavior in our daily life. However, we could not express our full intention if we could not understand fully how to make a proper request in the language that we are using. This study will make a contrastive analysis into the similarities and differences of using request speech act in English and Vietnamese daily conversations. In this study, the questionnaires are made into five different situations for English native speakers and Vietnamese native speakers to produce the requests in their languages. The analysis is divided into two parts. First, the ways English and Vietnamese people expressing request will be summarized in term of structures. Following, the similarities and differences of the request speech act made in two languages will be listed in tables and comparative figures.